2021
DOI: 10.1124/jpet.121.000514
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Specific Nonviral Gene Delivery of Fibroblast Growth Factor 21 Protein Expression in Mice Regulates Body Mass and White/Brown Fat Respiration

Abstract: Viral-mediated in vivo gene delivery methods currently dominate among therapeutic strategies within the clinical and experimental settings, albeit with well documented limitations arising from immunologic constraints. In this study, we demonstrate the utility of nonviral hepatotropic in vivo gene delivery of unpackaged expression constructs, including one encoding fibroblast growth factor 21 (FGF21). FGF21 is an important hepatokine whose expression positively correlates with therapeutic outcomes across variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“… 85 Although viral-mediated in vivo gene delivery can produce significant effects and is widely used, nonviral-mediated FGF21 expression plasmids can also be used for adipose cell transfection into the liver, providing new ideas and a basis for basic research even if the transfection time is increased. 86 Subsequently, another interesting study proved that the transduction of the exogenous FGF21 gene into high-fat-induced obesity mice by genetic engineering technology could effectively prevent fat accumulation, inhibit the formation of fatty liver, and greatly ameliorate insulin resistance. 87 Many studies have also proven that exogenous FGF21 has an excellent effect on lipid metabolism, the homeostasis of insulin, and energy balance.…”
Section: The Mediating Role Of Fgf21 In Lipid Metabolism In Adipose T...mentioning
confidence: 99%
“… 85 Although viral-mediated in vivo gene delivery can produce significant effects and is widely used, nonviral-mediated FGF21 expression plasmids can also be used for adipose cell transfection into the liver, providing new ideas and a basis for basic research even if the transfection time is increased. 86 Subsequently, another interesting study proved that the transduction of the exogenous FGF21 gene into high-fat-induced obesity mice by genetic engineering technology could effectively prevent fat accumulation, inhibit the formation of fatty liver, and greatly ameliorate insulin resistance. 87 Many studies have also proven that exogenous FGF21 has an excellent effect on lipid metabolism, the homeostasis of insulin, and energy balance.…”
Section: The Mediating Role Of Fgf21 In Lipid Metabolism In Adipose T...mentioning
confidence: 99%
“…Studies that investigated T2DM and FGF21 found that FGF21 can improve glucose homeostasis-related risk factors, such as glycated hemoglobin glycosylated hemoglobin A1c [142], insulin [97], and insulin resistance [108]. For obese animals and patients, preclinical and clinical trials have indicated the effect of FGF21 on improving the serum lipid profile and reducing body weight [173][174][175]. Regarding CVD, FGF21 can reduce the risk factors that influence the pathologic process of CVD, such as atherosclerosis [214], arterial stiffness [113], and blood pressure [86].…”
Section: Reduction Of Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…Many studies have chosen to increase FGF21 expression through genetic plasmids. One study reported that injection with a liver-specific FGF21 expression nonviral plasmid in FGF21 knockout mice can restore FGF21 expression and regulate body mass 174 . Another study utilized an adeno-associated viral vector to express FGF21 in mouse visceral adipose tissue, which resulted in reduced whole-body adiposity and adipose tissue macrophage inflammation 130 .…”
Section: Fgf21 and Metabolic Diseasesmentioning
confidence: 99%